Incidental finding of a large polypoidal gallbladder mass diagnosed as papillary adenocarcinoma – A case report. (May 2022) - Ghartimagar, Dilasma; Shrestha, Manish Kiran; Ruwanpathirana, Ramitha Eshan; Purbe, Dipika; Mishra, Sushil
Abstract: Introduction and importance: Lesions which project from the gallbladder wall into its lumen are known as gallbladder polyps. Nearly 5% of all adults have gallbladder polyps, the majority are pseudo-polyps with no neoplastic potential. Although gallbladder polyps are commonly found in cholecystectomy specimen, only a very few gallbladder polyps present as carcinoma in a polypoid lesion. Case presentation: A 48 years old male patient came for a routine health checkup and ultrasonography (USG) of abdomen showed incidental finding of a polypoid lesion measuring 43 × 28 mm in the gallbladder. Computed tomography scan revealed a soft tissue mass of similar size almost filling the lumen of the gallbladder and showed notable enhancement in post-contrast images. The mass was concluded to be suggestive of gallbladder carcinoma. Extended radical cholecystectomy was performed and histopathological examination of the polypoid lesion showed papillary adenocarcinoma with tumor staging of T2b. Clinical discussion: The prevalence of polypoid lesions of the gallbladder are reported to be 2–12% of all cholecystectomy specimens. Gallbladder polyps are one of the common USG findings in general population. It is difficult to differentiate between the benign and malignant polypoid lesions of the gallbladder solely depending on imaging studies. A size larger than 10 mm is the best indicator of malignancy. The most common malignant gallbladder polyp is adenocarcinoma. Conclusion: In majority of the cases, gallbladder polyp is an incidental finding. Even though most of the gallbladder polyps are benign in nature, cholecystectomy is the treatment of choice if the suspicion for malignancy is high. Highlights: Polypoid lesions of gallbladder are discovered incidentally. Presenting symptoms are mostly nonspecific. Ultrasonography of abdomen on routine health check-up showed the lesion. Most of the lesions are benign in nature but few present with malignant features. Polyps larger than 1 cm in size have higher chance of malignancy.